Is risk-taking in talented junior tennis players related to overuse injuries? - van der Sluis, A.; Brink, M. S.; Pluim, B.; Verhagen, E. A.; Elferink-Gemser, M. T.; Visscher, C. (Scandinavian Journal of Medicine & Science in Sports, 2016)
Overuse injuries are a serious problem in junior tennis. Gaining insight in age-specific risk factors can contribute to prevention. The developmental cognitive processes that take place during adolescence make talented players more inclined to take risks. This may be even more pronounced in the high performance culture in which they move. Therefore, this study focuses on the relationship between risk-taking and overuse injuries in talented tennis players. Seventy-three talented tennis players (45 boys and 28 girls, age 11-14 years) were monitored for 32 weeks, using the Oslo Sports Trauma Research Centre Questionnaire on Health Problems. Risk-taking was measured at the start of the season with the Iowa Gambling Task. Linear regression analyses were executed to predict (a) overuse injuries, (b) time loss overuse injuries and (c) overuse severity, by risk-taking, exposure time, and injury history. In boys, risk-taking contributed significantly to time loss overuse injuries [F(1,39) = 7.764, P = 0.008, R2 = 0.15] and to overuse severity [F(1,39) = 5.683, P = 0.022, with an R2 of 0.13] In girls, time loss overuse injuries [F(1,23) = 6.889, P = 0.018, R2 = 0.20] and overuse severity [F(1,23) = 7.287, P = 0.013, R2 = 0.24] were predicted by exposure time. Coaches and trainers should be aware that talented male tennis players who are inclined to take risks, are more likely to maintain risky behavioral patterns related to overuse injuries.